Analysis and optimization of the LAN network Using the Load Balancing Technique (Case Study: University of Muhammadiyah Palembang Campus) - Fani Agustina; Dedi Haryanto; Muhammad Ihsan (Universitas Islam Kuantan Singingi, 2025)
The development of Internet use on campus will automatically affect the need for bandwidth. To run the Internet smoothly, an adequate bandwidth quota is needed. If the usage exceeds the existing bandwidth service, the smooth Internet network will be stalled or stopped. The cessation or stagnation of Internet network services will certainly interfere with the process of comfort of lectures and student services on campus. Therefore, it is necessary to optimize the use of bandwidth in Internet use. Optimization can be done by using the load balancing setting path to balance when traffic is full where the main path will be backed up with another path from the backup ISP. The load balancing technique also has a positive effect on network availability. With more even load sharing, the risk of server failure can be reduced, leading to an increase in overall network availability. This shows that load balancing is essential in maintaining stable and reliable network performance, especially on systems involving multiple clients. Better Network Optimization with Load Balancing. Overall, this study shows that the application of load balancing can optimize the use of network resources. Through this technique, the network can operate more efficiently, reduce bottlenecks, and ensure a fair distribution of load between servers, leading to improved network performance. Based on the tests carried out in this study, the optimal application of load balancing is achieved. The implementation of load balancing can run without changing the existing network, and makes the connection run more optimally if there is an increase in network traffic due to a balanced division of connection lanes